2018
DOI: 10.1371/journal.pgen.1007592
|View full text |Cite
|
Sign up to set email alerts
|

Whi2 is a conserved negative regulator of TORC1 in response to low amino acids

Abstract: Yeast WHI2 was originally identified in a genetic screen for regulators of cell cycle arrest and later suggested to function in general stress responses. However, the function of Whi2 is unknown. Whi2 has predicted structure and sequence similarity to human KCTD family proteins, which have been implicated in several cancers and are causally associated with neurological disorders but are largely uncharacterized. The identification of conserved functions between these yeast and human proteins may provide insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 83 publications
(143 reference statements)
5
63
1
Order By: Relevance
“…A recent study showed that yeast Whi2 sharing a BTB domain homologous to that of human KCTD proteins is capable of inhibiting TORC1 under low amino acid conditions . Remarkably, human KCTD11 but not other KCTD proteins tested (KCTD7, KCTD8, KCTD11, KCTD12, and KCTD16) could suppress TORC1 activity when expressed in whi2 ‐deficient yeast and in mammalian cell lines under low amino acid conditions . Furthermore, knockdown of KCTD11 in HEK293 cells confirmed that KCTD11 is required to suppress mTORC1 during amino acid deprivation .…”
Section: Relevance Of Other Kctd Family Members To the Nervous Systemmentioning
confidence: 92%
See 4 more Smart Citations
“…A recent study showed that yeast Whi2 sharing a BTB domain homologous to that of human KCTD proteins is capable of inhibiting TORC1 under low amino acid conditions . Remarkably, human KCTD11 but not other KCTD proteins tested (KCTD7, KCTD8, KCTD11, KCTD12, and KCTD16) could suppress TORC1 activity when expressed in whi2 ‐deficient yeast and in mammalian cell lines under low amino acid conditions . Furthermore, knockdown of KCTD11 in HEK293 cells confirmed that KCTD11 is required to suppress mTORC1 during amino acid deprivation .…”
Section: Relevance Of Other Kctd Family Members To the Nervous Systemmentioning
confidence: 92%
“…Remarkably, human KCTD11 but not other KCTD proteins tested (KCTD7, KCTD8, KCTD11, KCTD12, and KCTD16) could suppress TORC1 activity when expressed in whi2 ‐deficient yeast and in mammalian cell lines under low amino acid conditions . Furthermore, knockdown of KCTD11 in HEK293 cells confirmed that KCTD11 is required to suppress mTORC1 during amino acid deprivation . The detailed molecular mechanism of how KCTD11 regulates mTORC1 activity is still unknown.…”
Section: Relevance Of Other Kctd Family Members To the Nervous Systemmentioning
confidence: 97%
See 3 more Smart Citations